Neolymphogenesis and Immunogistogochemical Study of Lymph Nodes in Breast Cancer - Sh. Kh. Gantsev; R. A. Rustamkhanov; Sh. R. Kzyrgalin; D. S. Tursumetov (Креативная хирургия и онкология, 2020)
Background. Our previous studies have shown that postnatally formed lymph nodes (PNFLN) can serve as a source of biological signals activating antitumour immune reactions and suppressing the spread of metastatic malignant cells.Aim. To determine the expression of CD3, CD20, CD68 in native, sentinel and postnatally induced lymph nodes of the axillary zone in breast cancer.Materials and methods. The study involved an analysis of digitalized images of the immunohistochemical expression of a fixed panel of antibodies CD3, CD20, CD68. The expression levels were assessed quantitatively by counting the expressed cells in each studied node for four main structural and functional zones.Results and Discussion. The results of a comparative immunohistochemical study of native, sentinel and postnatally induced lymph nodes showed that the content of CD3, CD20, CD68 demonstrates fundamental differences in different lymph node structures.Сonclusions 1. In postnatally induced lymph nodes, compared to native and sentinel lymph nodes, the distinct expression of antibodies to the main immunocompetent cells, which realize key immune responses in the lymph node, can indicate an increased functional status of the newly formed lymph nodes. 2. The study demonstrated a high level of antigenic stimulation of T and B lymphocytes in postnatally induced lymph nodes, as well as indicated a possible role of macrophage cells in the stimulation of neolymphogenesis and the formation of new lymph nodes. 3. The study provides the basis for further research into postnatal induced lymph nodes in cancer patients.